Functional polysaccharide lentinan: Role in anti-cancer therapies and management of carcinomas - Sagar Trivedi; Krishna Patel; Veena Belgamwar; Kamlesh Wadher (Elsevier, 2022)
Introduction: To conduct a retrospective data collection on prevalence of functional food lentinan as its role in anti-cancer therapies and management of carcinomas. Methods: The methodical review was carried out on various indexed databases Scopus, Web of sciences and Pubmed, in addition to the Google Scholar database. The work focuses on observational studies like anti-tumour, cytotoxic and immunomodulating of functional food lentinan. Results: World Health Organisation (WHO) classifies cancer as the second leading cause of death worldwide, approximately 1 in 6 deaths occurring are because of cancer, and WHO estimates ∼14.1 million new cancer cases and ∼10 million deaths per year. In recent years' natural products like mushrooms have emerged as an anti-cancer and immunomodulating agent and have overcome the drawbacks of conventional chemotherapeutic strategies. Similarly, Lentinan (LNT) a bioactive molecule obtained from Lentinus edodes with a chemical backbone of β -1, 3-glucan with two β -1, 6-glucose chains. The literature has suggested lentinan as a chemotherapeutic has improved quality of life and has promoted the efficacy of chemotherapy and radiation therapy during cancer treatment. The anti-tumour and biological response modifier and the ability of immunoregulation of lentinan have drawn the attraction to oncologists and pharmacologists Conclusion: Hence this review describes the possible mechanism of Lentinan as anti-tumour, cytotoxic and immunomodulating moiety in treating various cancers.